Relationship between Diet Pattern and Physical Activity with the Risk of Hypertension in Adolescents - Fike Deny Pamungkas; Dodik Hartono; Nur Hamim (KHD Production, 2024)
Hypertension is still a significant public health problem in Indonesia. One of the causes is poor diet and physical activity. Lifestyle modifications are made to prevent the risk of hypertension. This study aims to determine the correlation between diet and physical activity and hypertension risk (pre) in adolescents aged 15-18 years in the Senduro Health Center working area, Lumajang Regency. This study uses a type of quantitative research; the research design used is a descriptive correlation and uses a cross-sectional study design. The total population was 55 adolescents who visited the Sendero Health Center. Sampling was done on 48 adolescents using a purposive sampling technique. Data collected used a questionnaire and then analyzed using data analysis using chi-square test. This study found that adolescents with an unhealthy diet were 35 (70%), and adolescents who did light physical activity were 40 (80%). Adolescents who had blood pressure in the hypertension category were 37 (74%). The logistic regression statistical test results show the significance value is 0.003 (<0.05), indicating that adding independent variables can provide a significant correlation to the dependent variable model. So, there is a correlation between diet and physical activity with the risk of hypertension in adolescents. The results of this study are expected to provide insight and related knowledge to improve a diet pattern and do physical activity to maintain health and prevent hypertension.